Variation in epibiotic bacteria on two squat lobster species of Munidopsidae - Feng, Wenze; Wang, Minxiao; Dong, Dong; Hui, Min; Zhang, Huan; Fu, Lulu; Zhong, Zhaoshan; Xu, Zheng; Li, Chaolun (Frontiers in Microbiology, 2023)
The relationships between epibiotic bacteria on deep-sea hosts and host lifestyle factors are of particular interest in the field of deep-sea chemoautotrophic environmental adaptations. The squat lobsters Shinkaia crosnieri and Munidopsis verrilli are both dominant species in cold-seep ecosystems, and they have different distributions and feeding behaviors. These species may have evolved to have distinct epibiotic microbiota. Here, we compared the epibiotic bacterial communities on the Munidopsis verrilli carapace (MVcarapace), Shinkaia crosnieri carapace (SCcarapace), and Shinkaia crosnieri ventral plumose setae (SCsetae). The epibiotic bacteria on SCsetae were dense and diverse and had a multi-layer configuration, while those on MVcarapace and SCcarapace were sparse and had a monolayer configuration. Chemoautotrophic bacteria had the highest relative abundance in all epibiotic bacterial communities. The relative abundance of amplicon sequence variant 3 (ASV3; unknown species in order Thiotrichales), which is associated with sulfide oxidation, was significantly higher in SCsetae than MVcarapace and SCcarapace. Thiotrichales species seemed to be specifically enriched on SCsetae, potentially due to the synthetic substrate supply, adhesion preference, and host behaviors. We hypothesize that the Shinkaia crosnieri episymbionts use chemical fluxes near cold seeps more efficiently, thereby supporting the host’s nutrient strategies, resulting in a different distribution of the two species of squat lobster.